Leadership and Decision-Making Influence of Employee Performance - Rofi'ah, Rofi'ah; Lestari, Titi Ayem; Sulastri, Sulastri; Avira, Silvia (Action Research Literate, 2025)
Employees in a company are individuals who are employed by the company to carry out various tasks and responsibilities in order to achieve the company's goals. In realizing the company's goals, human resources are needed that have quality and are competitive, with good work quality it is expected to be able to produce high employee performance, employee performance is a measure of the extent to which an individual fulfills their duties and responsibilities in the workplace. Employee performance evaluation is important to measure productivity, contribution, and impact on the organization. Employee performance can be influenced by a combination of factors and can vary from individual to individual. Therefore, effective management involves understanding employee needs and potential, providing appropriate support, and implementing strategies that encourage continuous performance improvement. This study aims to determine the Influence of Leadership and Decision Making on Employee Performance with Leadership Style. The method used is a descriptive quantitative method with data collection techniques through questionnaire distribution. The author took the type of sample with a ratio of 10: 1, the number of samples used in this study was the number of indicators as much as 22 x 10 (max) = 220 respondents, Furthermore, to analyze the researcher used a Likert scale with the Analysis of Moment Structure (AMOS) analysis tool.